Retrieving Spent Cathodes from Lithium‐Ion Batteries through Flourishing Technologies. Issue 1 (27th November 2022) - Raj, Benjamin; Sahoo, Manoj Kumar; Nikoloski, Aleksandar; Singh, Pritam; Basu, Suddhasatwa; Mohapatra, Mamata
Abstract: The inherent advancement of lithium‐ion batteries (LIBs) in electronic gadgets is expanding exponentially, and the ongoing surge of electric vehicles (EVS) in the near future will result in an unprecedented amount of lithium waste. Used cathode materials contain hazardous metal toxic, polymer binder, and electrolytes, posing a serious risk to the environment and public health. For socio‐environmental reasons, it is required to recover all valuable metals or to immediately relithiate the used cathode materials by adding suitable salts in the stoichiometric ratio. As the consumption of batteries increases over time in daily life, recycling LIBs will become more and more crucial. Compared to the traditional hydrometallurgical and pyrometallurgical routes, direct recycling technologies can regenerate electrodes without using an intensive energy or chemicals, which saves money and reduces secondary waste. As a result, the authors emphasise direct relithiation methods for spent cathode relithiation, such as hydrothermal, ionothermal, electrochemical, and molten salts. In‐depth analysis and discussion are also given to the aforementioned approaches. The deactivation, disintegration, and separation processes used in the physical processing of black mass and other constituents are discussed. We reviewed the obstacles, possible commercialization of technology, and recommendations to the reviewer for the developing ecologically friendly recycling technology in the near future toward the circular economy. Abstract : Recover the waste: This article reviews the processing of spent lithium‐ion batteries by the existing technology and its beneficials.